Cenários prospectivos para a produção de leite bovino no estado do Rio Grande do Sul em 2030 - Trindade, Frederico dos Santos (Universidade do Vale do Rio dos Sinos, 2024)
This study presents prospective scenarios for milk production in the state of Rio Grande do Sul, Brazil, in 2030. Considering the importance of the dairy sector to Brazilian agribusiness and the challenges it faces, such as the decline in the number of producers and increasing global competitiveness, the research employs a scenario-based methodological approach to explore potential future trajectories. The study seeks to identify the factors influencing the sector's competitiveness, economic trends, and social changes that may impact dairy production. Employing a mixed-methods approach, data were collected through surveys with producers and technicians and conducted in the northwest mesoregion of Rio Grande do Sul, the state’s leading milk-producing region. Four main scenarios were developed: “Scenario 1: Competitive Transformation”, which envisions high technological adoption and productive efficiency aimed at the export market; “Scenario 2: Traditional Resilience”, characterized by stable production without significant technological advancements; “Scenario 3: Modernization Dilemma”, where producers adopt new technologies but struggle to achieve profitability; and “Scenario 4: Productive Collapse”, depicting small producers in vulnerable conditions, reliant on welfare policies. By constructing prospective scenario, the study provides insights into the variables impacting milk production, offering valuable perspectives for both the productive sector and academia.
Keywords: Cadeia agroindustrial do leite; Competitividade no agronegócio; Construção de cenários; Desenvolvimento rural; Gestão estratégica; Mercado de lácteos; Dairy agribusiness chain; Agribusiness competitiveness; Scenario construction; Rural development; Strategic management; Dairy market; ACCNPQ::Ciências Sociais Aplicadas::Administração